Aplicación web para la difusión turística del parque nacional Podocarpus. - Chamba Zaragocín, Wilman Patricio (2008)
his work with the theme: Web Application for tourism diffusion of Podocarpus National Park, has as its main objective to solve the lack of global tourism spread of Podocarpus National Park and thus reach potential tourists, governmental and nongovernmental organizations that may contribute to the care and conservation of this important nature reserve. The design of the entire Web application follows the object-oriented paradigm, so it was necessary to make a diagram use case, class diagram, prototype screens, diagrams robustness and sequence for each use case for this tool was used UML modeling, Enterprice Architect. For the design of the database, ie for the entity-relationship diagram, the tool was used DBDesigner. To build the application was used based on the Framework JSF, due to its protocol independence, which implies the separation between the model UI components and how these components are presented to the client, in addition to using this framework is it can be used in the context of the current web browsers. As programming environment NetBeans is used, which is an IDE available for free that offers full support for Java, also for handling database Hibernate, a tool that performs a mapping between Java classes to tables used database. For construction of virtual tours, floor plans was made in 2D of the three shelters Park using AutoCad, and then build the 3D file. In addition to the design of sensitive map panoramic photographs was taken, and a tour to the main entrances, paths and park areas, then build Macromedia Flash Player in was made. With the help of these tools it is able to build the Web Application for Podocarpus National Park, the same that is operating normally in the Ministry of Environment of Ecuador, specifically in its regional dependence of the provinces of Loja and Zamora Chinchipe. This application contains everything about the flora, fauna, hydrology, roads, trails, shelters, living areas, among others data Podocarpus National Park; also it has a sensible map of the geographical area of ​​the park, and virtual tours of the three main shelters (Vilcabamba, Bombuscaro and Cajanuma). Note that this application is properly documented with manuals and user programmer for better understanding, both in form and design.